Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

L'invention de l'hétérosexualité - Katz, Jonathan (EPEL, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Section: 236 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie

La menace : les lesbiennes contre-attaquent: de quelques critiques des féministes "lavande" - Katz, Jonathan (L'invention de l'hétérosexualité, 2001)
Keywords: approches et analyses; cours; discipline; fem1000; genre; histoire; hétérosexisme; identités; identités LGBTQIA2+; lesbianisme; premier cycle; sciences humaines; sexualité; systèmes d'oppressions; thématiques

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis